World Politics on Screen: Understanding International Relations through Popular Culture - Mark Sachleben (University Press of Kentucky, 2014)
international events affect our lives. Yet when most people think of television and international politics, they naturally assume that the connection has something to do with the news. This book starts from the premise that television and film can actually give us a deeper understanding about world politics. It will not argue that film and television can replace reading and research— but, by understanding how important political topics are covered in popular culture, we will have a better appreciation of how societies understand issues, problems, and potential solutions. To begin with, consider some important questions: What is the relationship between popular culture and politics? Why should those of us interested in politics pay attention to popular culture? The answers can be complex and multifaceted. Popular culture is a reflection of the way society believes the world operates. As the name suggests, popular culture has broad appeal. This is not a culture that is available to only a few; it is widely available to many people. Although popular culture has existed in all societies and all times, the unprecedented power of film and television as media has meant that the dissemination of messages now transcend time and place. Films and other moving-image mediums have the ability to convey a great deal of information and emotion, often without words. Ideas and reactions can be transmitted with a glance or a smile. Film and television are powerful ways to transmit messages and ideas. We live in a world in which the moving image is ubiquitous. The process of incorporating moving images into our popular culture began in the 1890s with the invention of motion pictures on filmstrips, and continued in the 1940s and 1950s with the mass production and acquisition of televisions by millions of people. Such images are constants in our lives today, with motion pictures being delivered to us by a plethora of electronic devices. While the method of delivering moving pictures to audiences continues to change, there is no doubt that the moving image will remain an important—and perhaps ever-increasing—facet of modern life.